THE LOCAL GOVERNMENT STRATEGY TO INCREASE COVERAGE FOR EXCLUSIVE BREASTFEEDING IN BOALEMO DISTRICT - Paweni, Robert (Universitas Negeri Medan, 2020)
This research aims at finding out and describing 1) the local government strategy to increase coverage for exclusive breastfeeding in Boalemo District and 2) factors supporting and hindering the strategy development of local government to increase coverage for exclusive breastfeeding in Boalemo district. This research applies qualitative method. Data collection uses interview, observation, and documentation. Based on the findings, it concludes that there are several things to be done by the local government in increasing coverage for exclusive breastfeeding, including enacting the local regulation for exclusive breastfeeding program, deciding the target areas, systematically implementing exclusive breastfeeding program, and supervising the program. On the other hand, factors supporting and hindering the coverage for exclusive breastfeeding program are policy support, budget availability, the healthcare workers, knowledge factor, health service facilities, cultural factor, and promotion on infant formula. Keywords: Local Government Strategy; The Increasing of Exclusive Breastfeeding.